Reduced reactivation from dormancy but maintained lineage choice of human mesenchymal stem cells with donor age - Dexheimer, Verena; Müller, Sebastian; Braatz, Frank; Richter, Wiltrud (PLOS ONE, 2011)
Mesenchymal stem cells (MSC) are promising for cell-based regeneration therapies but up to date it is still controversial whether their function is maintained throughout ageing. Aim of this study was to address whether frequency, activation in vitro, replicative function, and in vitro lineage choice of MSC is maintained throughout ageing to answer the question whether MSC-based regeneration strategies should be restricted to younger individuals. MSC from bone marrow aspirates of 28 donors (5-80 years) were characterized regarding colony-forming unit-fibroblast (CFU-F) numbers, single cell cloning efficiency (SSCE), osteogenic, adipogenic and chondrogenic differentiation capacity in vitro. Alkaline phosphatase (ALP) activity, mineralization, Oil Red O content, proteoglycan- and collagen type II deposition were quantified. While CFU-F frequency was maintained, SSCE and early proliferation rate decreased significantly with advanced donor age. MSC with higher proliferation rate before start of induction showed stronger osteogenic, adipogenic and chondrogenic differentiation. MSC with high osteogenic capacity underwent better chondrogenesis and showed a trend to better adipogenesis. Lineage choice was, however, unaltered with age. Conclusion: Ageing influenced activation from dormancy and replicative function of MSC in a way that it may be more demanding to mobilize MSC to fast cell growth at advanced age. Since fast proliferation came along with high multilineage capacity, the proliferation status of expanded MSC rather than donor age may provide an argument to restrict MSC-based therapies to certain individuals.
Gesehen am 09.05.2022